IMPORTANCE OF SELECTION VARIETIES IN THE PRODUCTION OF ECOLOGICALLY CLEAN APPLE PRODUCTS - Sadigov, A. (Аграрний вісник Причорномор’я, 2024)
The article provides extensive information on the economic and biological characteristics of apple varieties cultivated in the conditions of the Guba-Khachmaz economic zone, introduced, and obtained through selection at the Scientific Research Institute of Fruit and Tea Growing, and on the mechanical composition of the soil in which they are cultivated, electrical conductivity, etc. indicators (nitrogen, phosphorus, Ca, humus, Ph). As a result of the study, the chemical and mechanical composition, tasting value, resistance to diseases and pests, as well as transport resistance of varieties grouped into summer (Zirve, Ziya, Lala, Nıgar), autumn (Marfa, Sülh) and winter (Giziltaj, Ulvi, Vatan, Zumrud, etc.) were determined, and varieties with high economic efficiency were selected. According to the productivity indicators, the varieties Zia (18 tons), Sülh (23 tons), Makhmeri, Chiraggala (25 tons), Elvin, Emil, Shabran (27 tons) and Sadaf (30 tons) stood out. The highest indicator in terms of the amount of soluble dry matter was recorded in Lale, Makhmeri, Davamli with 11.5%, Khazar with 11.7%, vitamin “C” was recorded in Emil, Sadaf with 4.35 mg/%, and Giziltaj, Makhmeri varieties with 4.61 mg/%. In terms of sugar content, the summer varieties Lale with 9.15%, the winter varieties Gobustan, Chiraggala, Giziltaj, Khazar, Makhmeri, Davamli, Emil, Elvin with 9.13-9.14% and Sadaf with 9.61% showed good results. Compared to other varieties, the highest yield of commercial varieties of the first group was observed in the varieties Gobustan, Ulvi, Nubar, Vatan, Emil, Elvin (75%), Giziltaj (76%), Chiraggala, Davamli, Makhmeri, Sadaf (77%) and Sevinj (78%). According to their transport resistance, Zirve, Ziya, Gobustan, Zumrud, Khazar, Eldar, Nubar, Vatan, Nuran, Sarvan, Chiraggala, Elvin, Payizlig Guba, Qishlig Guba, Shabran varieties were selected as medium transport resistance, while Qiziltaj, Ulvi, Makhmeri, Davamli, Emil, Sadaf and Sevinj varieties were selected as good transport resistance varieties.